Radiocarbon dating from DH-7B sediment core from the Dahu Lake, Ilan Plain - Abdur Rahman; Liang-Chi Wang; Kaoru Kashima; Hong-Chun Li; Huei-Fen Chen; Tien-Nan Yang (PANGAEA, 2025)
A 35-meter-long sediment core (DH-7B) was retrieved from Dahu Lake using a stainless-steel pipe mounted on a floating platform. The core was subsampled at 5-cm intervals with 1-cm thickness for diatom, stable isotope, and trace element analyses. To establish the core chronology, 11 samples containing peat and plant remains were collected during subsampling, oven-dried at 40?°C, and dated by Accelerator Mass Spectrometry (AMS) at the AMS Laboratory, National Taiwan University.
In: Rahman, A et al. (2025): Typhoon and climate history of northeastern Taiwan during mid to late Holocene: inferred through the Dahu Lake sediment core, Ilan Plain [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982469